Directive Speech Acts In The Film "The Addams Family (2019)" - Zulfa Zulfa; Nur Laily Hamadah; Tatu Siti Rohbiah (Jurnal Intelek Insan Cendikia, 2025)
This study investigates the different types and communicative purposes of directive speech acts articulated by the characters in the animated film The Addams Family (2019). As defined by John Searle (1979), directive speech acts are utterances used by speakers to influence listeners' actions, which include commands, requests, suggestions, and prohibitions the directive speech act classification proposed by Safitri et al. (2021). Using a qualitative descriptive methodology, this study systematically collected and categorized relevant dialogue excerpts from the film. The analysis shows that commands directives are the most frequently used forms, reflecting the unique traits of the characters and the contextual demands of the storyline. In addition to these dominant forms, other directive acts-such as prohibitions, requests, and suggestions also contribute meaningfully to the characters' interactions. The findings of this study enrich the scholarship of pragmatics by illustrating how directive language operates in fictional cinematic settings, thus providing valuable insights into the strategic use of language in media discourse.